2006
DOI: 10.1242/jeb.02314
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of voltage-gated ion channel subunits from cnidocytes of the Portuguese Man O'War Physalia physalis

Abstract: SUMMARY Cnidocytes were dissociated from the tentacles of the Portuguese Man O'War Physalia physalis using heat treatment, and purified using density centrifugation. Visual observation confirmed that these cnidocytes contained a nucleus, a cnidocyst and an apical stereocilium, confirming that the cells were intact. A cnidocyte-specific amplified cDNA library was then prepared using RNA isolated from the cnidocytes, and screened for voltage-gated ion channel subunits using conventional molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Our results combined with previous studies (15,16,23,29,55) show that the functional and molecular diversification of Shaker and KCNQ families of voltage-gated K + channels was largely complete before the divergence of cnidarians and bilaterians. Furthermore, Erg K + channels, which constitute one of three bilaterian Ether-a-go-go gene subfamilies, are also highly conserved on functional level between cnidarians and vertebrates (70).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results combined with previous studies (15,16,23,29,55) show that the functional and molecular diversification of Shaker and KCNQ families of voltage-gated K + channels was largely complete before the divergence of cnidarians and bilaterians. Furthermore, Erg K + channels, which constitute one of three bilaterian Ether-a-go-go gene subfamilies, are also highly conserved on functional level between cnidarians and vertebrates (70).…”
Section: Discussionsupporting
confidence: 79%
“…Nematostella Shaker channels have been extensively characterized and demonstrate functional conservation between hydrozoans, anthozoans, and bilaterians (15,16,55). To better understand the functional evolution of the Shaker family, we first functionally expressed Nematostella whole Shab, Shaw, and Shal channels in Xenopus oocytes.…”
Section: Resultsmentioning
confidence: 99%
“…There is also a pattern of high conservation for other voltage-gated K + channels, including the Shaker, Shal and Shaw families, which encode A-currents and delayed rectifiers and probably play important roles in action potential repolarization and patterning (Bouchard et al, 2006;Jegla and Salkoff, 1997;Jegla et al, 2012;Sand et al, 2011). Therefore, the high molecular conservation of channel genes between cnidarians and bilaterians extends to functional conservation, at least at the level of channel biophysics.…”
Section: Research Articlementioning
confidence: 99%
“…1). The recently cloned K V 1 channel from the Portuguese Man-o-War, Physalia physalis, also lacks the first acidic residue in S2 (S231 in PpK v 1) and has a shortened S4 (Bouchard et al, 2006), suggesting that these two structural differences may reflect a conserved variant of K V 1 channel architecture in the class Hydrozoa. Previous mutagenesis analysis in jShak1 (Grigoriev et al, 1997) demonstrated that the addition of length and charge in the S4 voltage sensor, to either side of the conserved K294 residue (K374 in Drosophila Shaker) had complex effects on channel properties, but did not simply shift the voltage sensitivity of jShak1 to the range observed for vertebrate K V 1 channels.…”
Section: Introductionmentioning
confidence: 99%